The effect of plant density on productivity of the grain sorghum variety ‘Ataman’ in the Lugansk region - V. V. Kovtunov; A. V. Baranovsky (Зерновое хозяйство России)
Frequently occured dry years and a sharp decrease of productivity and gross harvests of grain crops require scientifically grounded selection of grain crops that stabilize its production. Currently, the drought resistant sorghum varieties can become a good alternative for the main spring grain crops. In the Luhansk region, the average annual amount of precipitation is 475 mm, which confirms the advantage in growing grain sorghum over other spring grain crops. However, plant density of the modern recommended grain sorghum varieties related to specific soil and climatic conditions has not yet been studied enough. The purpose of the current research was to study and highlight the optimal plant density of the grain sorghum variety ‘Ataman' in the conditions of the Luhansk region. The study was carried out on the basis of the Luhansk National Agricultural University in 2018-2019. Sorghum was sown at the rate of 350.000 germinated grains per hectare. In a sprouting phase, plant density was manually formed according to the experimental scheme (from 40 to 340 thousand/ha). The study of the new early-ripening grain sorghum variety ‘Ataman', developed by the FSBSI “Agricultural Research Center “Donskoy”, showed that regardless of the moisture supply and the thermal regime during vegetation, it was advisable to grow this variety with a plant density of 140-220 thousand/ha. In the conditions of the Luhansk region with mineral nutrition N60P40, it was possible to form the productivity of the grain sorghum variety ‘Ataman' at the level of 5.06-5.52 t/ha of grain and more. The vegetation period of the variety ‘Ataman', depending on the plant density and weather/climatic conditions of the year, was 90-102 days, which made it possible to harvest it in the 1st-2nd decade of September without additional drying of the grain. The variety did not lodge or shed its grain, and was also resistant to grain aphids.